La difficile articulation du présentiel et de la distance dans le cadre d'un cours hybride en master - Thierry Soubrié (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
Classes combining face to face and distance teaching are far from being widespread. According to (Charlier et al., 2004), the first environments of this kind have appeared in France around 1997, as they were perceived as a possible alternative to distance teaching exclusively. In terms of pedagogic innovation however, the potentialities of these environments begin to be emphasised, in particular in a recent book published in the United States (Graham, 2006). Two issues must then be considered: what are the respective advantages of these two training modes and how can we make them complementary. In this article, I will try to answer these questions, through the analysis of an experimental hybrid module being offered on the first year of the Masters: "Information technology and communication for teaching/learning of French as a foreign language".